Governance of Artificial Intelligence in the EU - Mitrevska, Olgica; Antal, Jarolím, 1986-; Bič, Josef; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
Why and how emerging technologies should be regulated is a current debate. This paper adapts the multiple streams approach - often used to explain policymaking processes to the regulation of artificial intelligence. It traces the formulation of proposals, political developments and problem framing in the European Union. It analyses the position of the European Commission as a policy entrepreneur. It also searches for legal harmonization of problem definition regarding AI. It concludes that a common definition has not been reached, even after visible efforts. However, it has been pushed on the agenda thanks to the GDPR.
Vedoucí práce: Jarolím Antal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: evropská ekonomická integrace [obor dipl. práce]; diplomové práce; master's theses